Analisis Ketercapaian Indikator pada Standar Pendidik dan Tenaga Kependidikan di SMP Muhammadiyah Cipanas - Iwan Setiawan (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2019)
The study was conducted to analyze the achievement of standards of educators and education personnel. This is important to discuss to ensure the achievement of an institution in eight national education standards. This research method uses descriptive method. The participation of this research was 25 educators and education staff in SMP Muhammadiyah Cipanas Middle School, Cianjur Regency. The instrument used refers to nineteen standard indicators of educators and education personnel in the form of interview guidelines. The conclusions of this study are (1) the achievement profile of the standard indicators of educators and education personnel, showing varied results with an average achievement of 83%; (2) indicators that have not reached the maximum score are certification teachers, BK teacher professionalism, BK Teacher Ratio, and Library Staff. Recommendations on the results of this study need an in-depth study of certification teachers and the ratio of BK teachers in schools.